Can a Before-School Physical Activity Program Decrease Bullying Victimization in Disadvantaged Children? the Active-Start Study [¿Puede Un Programa de Actividad Física Antes de la Escuela Disminuir la Victimización por Bullying en Niños Desfavorecidos? Estudio Active-Start] - Fernandez-Vergara, O; Garcia-Hermoso, A; Gonzalez-Calderon, N; Hormazabal-Aguayo, I (Elsevier Doyma, 2019)
Background/Objective: To test the effectiveness of an 8-week before-school physical activity program to reduce bullying victimization among a group of socially disadvantaged children in the Active-Start study. Method: A non-blinded randomized controlled trial was conducted in three public schools classified as highly vulnerable and located in a deprived area of Santiago (Chile). A total of 5 classes participated, totaling 170 fourth grade children. The intervention was delivered before starting the first school-class (8:00–8:30 a.m.). The program lasted for 8 weeks. Primary outcome measurement on bullying victimization was assessed by the CUBE questionnaire at baseline and post-intervention. Results: There was a statistically significant reduction in the probability of suffering physical bullying (OR= 0.18, 95% CI, 0.04-0.82; p= .027) and verbal bullying (OR=0.13, 95% CI, 0.02-0.97; p= .046) after the 8-week program. Conclusions: Participation in an 8-week before-school physical activity intervention implemented in schools located in a disadvantaged district in Santiago (Chile) resulted in lower levels of bullying victimization among study participants. The Active-Start program may be a feasible and potentially scalable intervention option to improve the climate and pro-sociality environment at schools. © 2019